An Eco-Friendly Synthesis of Silver Nanoparticles Using Extract of Capsicum chinense Jacq. as A Bio-reducing Agent - Mohamad Rafi; Boyfannie Ivan Putra; Hermin Sulistyarti; Rurini Retnowati (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2023)
Silver nanoparticles (AgNPs) have become popular due to their unique properties that can be used as biosensors, composite fibers, semiconductor materials, and other medical applications. Green synthesis of AgNPs using natural reagents from plant extract offers advantages as an efficient and environmentally friendly technique by which the compounds from the extract perform as bio-reductor for silver ions and the capping agent for stabilizing the AgNPs. Therefore, the purpose of the study was to conduct the synthesis of AgNPs by utilizing an extract of Capsicum chinensie Jacq as the bioreductor. The effect of extract concentrations, duration of exposure to sunlight, and temperatures on AgNPs formation was studied to obtain the optimum synthesis condition. The biosynthesized AgNPs characteristics were analyzed using UV-Vis Spectrophotometry, FTIR, SEM, X-Ray Diffraction, and PSA. The results showed that the higher extract concentration produced smaller AgNPs. The synthesis under sunlight exposure showed more product of AgNPs compared to heating on a hot plate. The optimum conditions of biosynthesis of AgNPs were attained at the volume ratio of extract (20%) and AgNO3 (1mM) of 1:1 and duration of sunlight exposure of 90 min, resulting in AgNPs characterized with maximum wavelength 422 nm and average particle sizes of 67.94 nm.